Improving the UI/UX Design Quality of the Informatics Engineering Study Program Website at Universitas Bina Darma Using the Design Thinking Method - Kiagus Fallah Abrar Al Karim; Devi Udariansyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Rapid advances in information technology have transformed multiple sectors, particularly education, where digital platforms play an increasingly vital role in academic operations. Study program websites now serve as primary channels for information dissemination and communication between institutions and their stakeholders. Yet the Informatics Engineering Study Program website at Universitas Bina Darma faces notable usability problems affecting both interface design and user experience quality. A heuristic evaluation survey of 100 students identified several critical issues: absent active menu indicators that hinder navigation tracking, unattractive visual layouts that reduce user engagement, and ambiguous icons and terminology that create confusion during interaction. To address these challenges, researchers employed the Design Thinking framework—a user-centered methodology that emphasizes empathy, ideation, and iterative testing. The framework guided the development of a redesigned prototype, which underwent rigorous evaluation through the Maze platform across four distinct user task scenarios covering key website functions. Test outcomes demonstrated 100% task completion rates among participants, with an average usability score of 89, placing the design in the excellent category. The redesigned interface delivers substantially improved user experience through enhanced navigation clarity, better visual hierarchy, and more intuitive interaction patterns. These improvements establish a solid groundwork for continued development and eventual implementation of systems, offering practical solutions that can be adapted for similar academic website redesign projects.